(untitled) (Elmergib Journal of Human Sciences, 2025)
The present study aims to explore the perceptions of Libyan students towards using Facebook storytelling videos in enhancing their vocabulary skills. Furthermore, it is aimed to discover the benefit of Facebook storytelling videos used by Libyan Students in enhancing their vocabulary skills. This study used a mixed method design. The researcher obtained quantitative data first by data gathering, analyzing and taking precedence in explanatory mixed method designs. Furthermore, the researcher used qualitative method to fully analyze the conclusions of the quantitative data. The researcher used a close-ended questionnaire as well as semi-structured interview as instruments in this study. The participants were twenty-five Libyan students studying at the fourth year at English language department, Faculty of Education, Mesalata, Elmergib University during the academic year 2024-2025. Seven participants were male and eighteen participants were female. twenty-five Participants were chosen to conduct a close-ended questionnaire as well as the researcher conducted semi-structured interviews with six participants out of twenty-five participants who were chosen to represent other students based on their engagement in class and their scores. This study revealed that Libyan students are using Facebook as a popular platform for enhancing their vocabulary in English. The findings showed that Facebook platform is a very active and easy way for university students who want to improve their language skills. Also, Libyan students enjoy learning by watching Facebook Storytelling videos. The researcher also found out that Facebook storytelling videos is a motivational tool to learn new words and know their meaning.